Digital Marketing and Consumer Millennials : A Comparative Study of Men, Women, and Transgender Consumers' Buying Behaviour in Punjab - Sharma, Pooja; Gupta, Sushant; Kapoor, Deepika (Indian Journal of Marketing, 2020)
Millennials play an enormous role in digital marketing as they are the ones who have grown up in a social media world. They are considered as a key target market for many digital marketing campaigns. Therefore, it is important to study the buying behavior of these consumers to know about their tastes, preferences, and expectations. The purpose of this study was to determine the most preferred digital marketing strategies by consumer millennials and also to compare the buying behavior of men, women, and transgender consumers in Punjab. There are many studies which have focused mainly on male and female buying behavior, but hardly any studies have been conducted, which have focused on comparing the buying behavior of men, women, and transgender consumers. This study considered transgenders also as this is the community which has different tastes and preferences as compared to other genders. The sample size for the purpose of the present study consisted of 250 respondents. The study concluded that the most preferred digital marketing platform by men was Instagram ; whereas, for women, the most preferred platforms were videos, blogs, and social media posts. On the other hand, transgenders' purchase decisions were mostly influenced by Instagram followed by Facebook. The study provides the implications to the marketing companies to focus on the buying behavior of men, women, and transgenders to market their products.